Losing Ground: 2010 Report Card on Apprentices in the Construction Trades - (:unkn) unknown (My University, 2010)
This report provides racial/ethnicity and gender data on apprentices by construction trade joint apprenticeship committee, as of January 2010, based on data provided to the NAACP – Milwaukee Branch by the Wisconsin Department of Workforce Development Bureau of Apprenticeship Standards. The hiring patterns of 16 union joint apprenticeship committees serving the Milwaukee area are analyzed and report cards provided for 341 contractors with apprentices. A second analysis examines the hiring patterns of 102 nonunion contractors with apprentices. This is the third report prepared by the NAACP and ETI to track hiring and training of apprentices in the construction trades. Construction contractors receiving federal stimulus funds under the 2009 American Recovery and Reinvestment Act are obligated to meet affirmative action provisions contained in Executive Order 11246, with enforcement through the U.S. Department of Labor Office of Federal Contract Compliance Programs (OFCCP).
Keywords: affirmative action; construction trades; apprenticeships; job training